Effects of 24 Years of Conservation Tillage Systems on Soil Organic Carbon and Soil Productivity - Kenneth R. Olson; Stephen A. Ebelhar; James M. Lang (Applied and Environmental Soil Science)
The 24-year study was conducted in southern Illinois (USA) on land similar to that being removed from Conservation Reserve Program (CRP) to evaluate the effects of conservation tillage systems on: (1) amount and rates of soil organic carbon (SOC) storage and retention, (2) the long-term corn and soybean yields, and (3) maintenance and restoration of soil productivity of previously eroded soils. The no-till (NT) plots did store and retain 7.8 Mg C ha−1 more and chisel plow (CP) −1.6 Mg C ha−1 less SOC in the soil than moldboard plow (MP) during the 24 years. However, no SOC sequestration occurred in the sloping and eroding NT, CP, and MP plots since the SOC level of the plot area was greater at the start of the experiment than at the end. The NT plots actually lost a total of −1.2 Mg C ha−1, the CP lost −9.9 Mg C ha−1, and the MP lost −8.2 Mg C ha−1 during the 24-year study. The long-term productivity of NT compared favorably with that of MP and CP systems.